2016
DOI: 10.1289/ehp.1409392
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Ambient Temperature in East Asian Countries: A Time-Stratified Case-Crossover Analysis

Abstract: BackgroundA limited number of studies suggest that ambient temperature contributes to suicide; these studies typically focus on a single nation and use temporally and spatially aggregated data.ObjectiveWe evaluated the association between ambient temperature and suicide in multiple cities in three East Asian countries.MethodsA time-stratified case-crossover method was used to explore the relationship between temperature and suicide, adjusting for potential time-varying confounders and time-invariant individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
61
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 41 publications
15
61
1
1
Order By: Relevance
“…Our results support the existence of a psychological link between heat exposure and mental health that could be a contributing factor behind the association between heat exposure 14 and suicide mortality (Kim et al, 2016;Maes et al, 1994;Page et al, 2007;Qi et al, 2015). Furthermore, our results are consistent with, and provide evidence of, mechanisms mediating the effect of temperature on economic activity and interpersonal aggression.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results support the existence of a psychological link between heat exposure and mental health that could be a contributing factor behind the association between heat exposure 14 and suicide mortality (Kim et al, 2016;Maes et al, 1994;Page et al, 2007;Qi et al, 2015). Furthermore, our results are consistent with, and provide evidence of, mechanisms mediating the effect of temperature on economic activity and interpersonal aggression.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have focused on suicide mortality and indicate that heat exposure is associated with increased suicide rates (Basagaña et al, 2011;Kim et al, 2016;Maes, De Meyer, Thompson, Peeters, & Cosyns, 1994;Page, Hajat, & Kovats, 2007;Qi, Hu, Page, & Tong, 2015). One study has found an impact of heat exposure on hospital admissions for mental and behavioral disorders (Hansen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The results of studies that have addressed death due to one or more external causes separately, are consistent with these results. For example, several studies have examined the effect of temperature on death due to suicide and have shown that high temperatures are associated with an increase in suicides [32] [33] [34].…”
Section: Discussionmentioning
confidence: 99%
“…Together, these direct and indirect impacts pose mental health risks for ado lescents, including post-traumatic stress disorder, depression, anxiety, sleep disorders and even suicide. [21][22][23] Heat exposure can also increase irritability, aggression and violence, [24] a major concern given the rates of physical and sexual violence in schools in SA, both pupil-onpupil and between teacher and pupil. Extreme weather events such as storms, droughts and wildfires have been strongly linked with mental health conditions in adolescents, which commonly persist into adulthood.…”
Section: Guest Editorialmentioning
confidence: 99%